Capacidade funcional para o exercício e nível de capacidade física de crianças e adolescentes com anemia falciforme - Lima, Hugo Nivaldo Melo Almeida (2015)
Sickle cell disease (SCD) is a disease with great clinical and epidemiological importance, various clinical manifestations are commonly observed in patients with SCD, and these manifestations seem to be associated with a lower exercise capacity. However, little is known about the level of physical activity (PA) and its relationship to physical performance in children and adolescents with SCA. This dissertation consists of two original articles. In the first article, "Determinants of the maximum walking distance of the six-minute walking test in children and adolescents with sickle cell anemia", the main findings were that the determinants of the maximum distance the 6-minute walk test (6MWT) in children and adolescents with SCD are related positively with age and negatively with BMI. In addition, an equation was established to provide for maximum distance. 6MWD = 487.7 + (age 18.3) - (BMI * 12). The reliability of this equation was assessed using the Bland and Altman plot in a second, independent group of patients. The second article, "Physical activity level by questionnaire and physical performance by six-minute walking test in children and adolescents with sickle cell anemia", compared the PA, assessed using the Physical Activity Questionnaire for Older Children and Adolescents (PAQs), and physical performance, measured by the 6MWT in children and adolescents with and without SCD, and to investigate possible relationships between PA and physical performance in both groups. In this study it was observed that children and adolescents with SCD have a PA lower than in healthy individuals, as measured by PAQs and compare the physical performance in the 6MWT, we observed that the group with SCD presented clinically worse performance in the test, compared healthy subjects. Collectively, these findings may state that patients with sickle cell anemia present physical fitness to exercise below normal. The main determinant for this abnormal exercise capacity were age and BMI. This fact may mark out research associated with causality less physical activity in this population.